The molecular basis of EPCAM expression loss in Lynch syndrome-associated tumors - Huth, Cathrin; Kloor, Matthias; Voigt, Anita Yvonne; Bozukova, Gergana; Evers, Christina; Gaspar, Harald; Tariverdian, Mirjam; Schirmacher, Peter; Knebel Doeberitz, Magnus von; Bläker, Hendrik (Modern pathology, 2012)
Germline deletions affecting the Epithelial cell adhesion molecule (EPCAM) gene lead to silencing of MSH2 and cause Lynch syndrome. We have recently reported that lack of EPCAM expression occurs in many, but not all tumors from Lynch syndrome patients with EPCAM germline deletions. The differences in EPCAM expression were not related to the localization of EPCAM germline deletions. We therefore hypothesized that the type of the second somatic hit, which leads to MSH2 inactivation during tumor development, determines EPCAM expression in the tumor cells. To test this hypothesis and to evaluate whether lack of EPCAM expression can already be detected in Lynch syndrome-associated adenomas, we analyzed four carcinomas and two adenomas from EPCAM germline deletion carriers for EPCAM protein expression and allelic deletion status of the EPCAM gene region by multiplex ligation-dependent probe amplification. In four out of six tumors we observed lack of EPCAM expression accompanied by biallelic deletions affecting the EPCAM gene. In contrast, monoallelic retention of the EPCAM gene was observed in the remaining two tumors with retained EPCAM protein expression. These results demonstrate that EPCAM expression in tumors from EPCAM deletion carriers depends on the localization of the second somatic hit that inactivates MSH2. Moreover, we report lack of EPCAM protein expression in a colorectal adenoma, suggesting that EPCAM immunohistochemistry may detect EPCAM germline deletions already at a precancerous stage.
Gesehen am 12.10.2018